Effet D’un Extrait Aqueux De Pseudarthria Hookeri Wight & Arn. (Fabaceae) Sur La Glycemie Et Sur La Liberation Et Le Stockage Du Glucose Hepatique De Rats Diabetiques - Kahou Bi, Gohi Parfait; Claude Abo, Kouakou Jean; Irie Bi, Jean Severin (European Scientific Journal, ESJ, 2016)
Pseudarthria hookeri (Fabaceae) is a plant used in traditional medicine in Ivory Coast to treat diabetes. This study aims to evaluate the antidiabetic effects of the aqueous extract of Pseudarthria hookeri (EAPh) on the release and storage of hepatic glucose in alloxan induced diabetic rats. The administration of EAPh, at a dose of 1200 mg/kg body weight for 28 days, leads to a significant decrease of glycaemia in diabetic rats. The oral administration of EAPh, at doses of 800 mg/kg, 1000 mg/kg and 1200 mg/kg body weight, reduced for 60 min, in a dose-dependent manner, the release of hepatic glucose in normoglycemic rats. Moreover, for 90 days of treatment, EAPh significantly promotes the storage of hepatic glucose in diabetic rats. It appears that the aqueous extract of Pseudarthria hookeri has antidiabetic properties and acts by promoting the storage of hepatic glucose (glycogenesis), and by inhibiting the release of glucose from the liver (glycogenolysis). These results justify the use of Pseudarthria hookeri in traditional medicine to effectively treat diabetes.